2010
DOI: 10.1002/esp.1953
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of climate change impacts on Saint‐Lawrence River tributaries

Abstract: The impacts of climate-induced changes in discharge and base level in three tributaries of the Saint-Lawrence River, Québec, Canada, are modelled for the period 2010-2099 using a one-dimensional morphodynamic model. Changes in channel stability and bed-material delivery to the Saint-Lawrence River over this period are simulated for all combinations of seven tributary hydrological regimes (present-day and those predicted using three global climate models and two greenhouse gas emission scenarios) and three scen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(70 citation statements)
references
References 55 publications
(79 reference statements)
4
66
0
Order By: Relevance
“…Figure 4 also highlights the increase in the highest sediment yields, in particular for the 2070-2099 High emissions scenario (totals greater than 5 000 000 m 3 ). Such increases in sediment associated with climatic increases in rainfall are broadly in line with soil erosion studies (Favis-Mortlock and Guerra, 1999;Chaplot, 2007) and channel models (Verhaar et al, 2010). (Holm, 1979 ) is shown in white in the left hand panel; the variability in these simulations comes from stochastic variability alone.…”
Section: Integration Of Climate and Geomorphic Modelssupporting
confidence: 74%
See 1 more Smart Citation
“…Figure 4 also highlights the increase in the highest sediment yields, in particular for the 2070-2099 High emissions scenario (totals greater than 5 000 000 m 3 ). Such increases in sediment associated with climatic increases in rainfall are broadly in line with soil erosion studies (Favis-Mortlock and Guerra, 1999;Chaplot, 2007) and channel models (Verhaar et al, 2010). (Holm, 1979 ) is shown in white in the left hand panel; the variability in these simulations comes from stochastic variability alone.…”
Section: Integration Of Climate and Geomorphic Modelssupporting
confidence: 74%
“…Channel and upstream sediment inputs are considered, but hillslopes are not explicitly modelled (and linked) as with landscape evolution models. Verhaar et al (2010) modelled future changes in the Saint-Lawrence River, Quebec, using a one dimensional hydraulic model. Seven scenarios of future discharges under different climate change conditions were simulated and all led to increases in sediment delivery.…”
Section: T J Coulthard Et Al: Using the Ukcp09 Probabilistic Scenamentioning
confidence: 99%
“…However, flood risk can also partly be compensated for by bed incision during more frequent extreme events (Verhaar et al, 2011). Increasing average bed material and suspended sediment delivery have also been predicted for the St. Lawrence River (Table 1: Verhaar et al, 2010Verhaar et al, , 2011. Even without change to base level, increases in average bed material delivery are expected according to these studies, although the magnitude of simulated changes depended on the choice of GCM and the trend over time related to whether the river is currently aggrading, degrading or in equilibrium (Verhaar et al, , 2011.…”
Section: Input Data and External Forcing Conditionsmentioning
confidence: 93%
“…Even without change to base level, increases in average bed material delivery are expected according to these studies, although the magnitude of simulated changes depended on the choice of GCM and the trend over time related to whether the river is currently aggrading, degrading or in equilibrium (Verhaar et al, , 2011. Verhaar et al (2010) showed that a fall in base level leads to degradation and increased sediment delivery in river channels that are currently either aggrading or in equilibrium, amplifying the effects of climate change on sediment delivery. Of particular interest is the finding that the magnitude of base level fall is more important for future channel development than its duration, that is, whether the fall was sudden or more prolonged.…”
Section: Input Data and External Forcing Conditionsmentioning
confidence: 96%
“…Sung et al (2006), De Wit et al (2007 and Millerd (2011) focused on water-level modification due to variations in hydrology that would eventually impact navigation. Bed-level change effects on navigation channels were considered to a lesser extent by Verhaar et al (2010).…”
Section: Introductionmentioning
confidence: 99%